PENGARUH RELIABILITY, RESPONSIVENESS, SECURITY AND SAFETY TERHADAP SATISFACTION NASABAH BANK SYARIAH INDONESIA PADA MASYARAKAT SOLO RAYA - Novia Mayasari; Meilana Widyaningsih; Ajeng Karunia Ramadhani (LPPM - STIE SAKTI ALAM KERINCI, 2023)
This study aims to determine the effect of reliability, responsiveness, security and safety onsatisfaction at Bank Syariah Indonesia. This study used primary data and analyzed using quantitativemethods with statistical t tests. The population is part of the customers of Bank Syariah IndonesiaSolo Raya with a sample of 100 respondents. Based on the results of the analysis obtained,conclusions can be drawn based on the t-test for the reliability variable (X1) the value of t count is3,587 > t table 1,900 with a significant level of 0.001 <0.05 meaning, there is a significant influencebetween the reliability variable on satisfaction. Meanwhile, the variable perception of responsiveness(X2) has no effect on satisfaction because it has a significant value of 0.114 > 0.05 or a t-count valueof 1.596 < t-table 1.900 so H0 is accepted. And the variable perception of security and safety (X3)has an effect on satisfaction in this study because it has a significant value of 0.000 <0.05 or a t-countvalue of 5.683 > t-table 1.900 so H0 is rejected. Based on the f-test, there is a count of 214,419 with asig f value of 0.00 <0.05, then H0 is rejected, H1 is accepted. This means that simultaneouslyreliability (X1), responsiveness (X2), security and safety (X3) have a significant influence onsatisfaction (Y).